Characterization of Dyspnea in Veteran Lung Cancer Survivors Following Curative-Intent Therapy. Issue 2 (March 2020) - Ha, Duc; Ries, Andrew L.
Abstract : Purpose: Dyspnea is highly prevalent in lung cancer survivors following curative-intent therapy. We aimed to identify clinical predictors or determinants of dyspnea and characterize its relationship with functional exercise capacity (EC). Methods: In an analysis of data from a cross-sectional study of lung cancer survivors at the VA San Diego Healthcare System who completed curative-intent therapy for stage I-IIIA disease ≥1 mo previously, we tested a thorough list of comorbidities, lung function, and lung cancer characteristics. We assessed dyspnea using the European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire Lung Cancer Module 13 (LC13) and functional EC using the 6-minute walk. We replicated results with the University of California San Diego Shortness of Breath Questionnaire. Results: In 75 participants at a median of 12 mo since treatment completion, the mean ± SD LC13-Dyspnea score was 35.3 ± 26.2; 60% had abnormally high dyspnea. In multivariable linear regression analyses, significant clinical predictors or determinants of dyspnea were (β [95% CI]) psychiatric illness (−20.8 [−32.4 to −9.09]), heart failure with reduced ejection fraction (−15.5 [−28.0 to −2.97]), and forced expiratory volume in the first second of expiration (−0.28 [−0.49 to −0.06]). Dyspnea was an independent predictor of functional EC (−1.54 [−2.43 to −0.64]). These results were similar with the University of California San Diego Shortness of Breath Questionnaire. Conclusion: We identified clinical predictors or determinants of dyspnea that have pathophysiological bases. Dyspnea was independently associated with functional EC. These results have implications in efforts to reduce dyspnea and improve exercise behavior and functional EC in lung cancer survivors following curative-intent therapy. Abstract : Supplemental Digital Content is Available in the Text.This cross-sectional study identified clinical predictors or determinants of dyspnea in veteran lung cancer survivors post-curative-intent therapy. In 75 participants, psychiatric illness, heart failure, and forced expiratory volume in the first second of expiration were independently associated with dyspnea. Dyspnea was an independent predictor of functional exercise capacity. These results have implications in rehabilitation and lung cancer survivorship.